Severe allergic reaction to human insulin in the patient with diabetic ketoacidosis - Nese Colak Oray; Basak Bayram; Emel Altintas; Semra Sivrikaya; Yusuf Savran (Turkish Journal of Emergency Medicine, 2018)
Diabetic ketoacidosis (DKA) is an acute and major life-threatening complication of diabetes mellitus. Fluid resuscitation, insulin therapy, and electrolyte replacement are essential for DKA treatment. Rarely, life threatening allergic reactions might develop in a patient treated with insulin. If anaphylaxis develops after insulin, the DKA treatment options are restricted. A limited number of case reports have been reported in patients with severe anaphylactic reactions to human insulin who were then treated with synthetic insulin analogues. We present a case of a 45-year-old male patient with allergic reactions to human insulin. The patient was successfully treated with insulin aspart and hemodialysis. Keywords: Diabetic ketoacidosis, Regular insulin, Allergic reaction, Emergency treatment, Insulin aspart